Revisiting the role of calcite in Spondylus crassisquama shell - Rodriguez S. (2017)
The authors would like to thank the vice-rectorate for research of the Pontificia Universidad Católica del Perú and the Peruvian Council of Science and Technology (Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica–Fondo Nacional de Desarrollo Científico y Tecnológico) for financial support. Dr Vicente Lorenzo from the Polytechnical University of Madrid is acknowledged for providing technical support during the microhardness tests.